Muslim Women, Counselling and Rights: An Islamic Overview - Salihi Ashiru Musa; Bello Ali (Demak Universal Journal of Islam and Sharia, 2024)
This paper titled Muslim Women, counselling and Rights an Islamic Overview discussed the counselling of Muslim women and their rights in regards to the person counselling the women. Counsellor offers services for the wellbeing of individuals irrespective of gender. The paper examines the Conventional and Islamic perspectives of counselling about women and some of their rights. The paper identifies that both conventional and Islamic perspectives did not differ in addressing women’s challenges. However, the two perspectives differ in approaches, techniques skills, and application. The paper also highlights some of the rights of Muslim women in terms of counselling which is not found in the Western notion of counselling of women. Also discussed are the approaches to counselling women particularly Muslim women. The study adopted a qualitative research method where secondary sources of data were utilised and analysed as its methods of analysis. It is concluded that both perspective is found to be effective and therefore it is recommended that counsellors should be familiar with both.